Estudio de factibilidad para la creación de una empresa productora y comercializadora de hortalizas de origen orgánico, cantón Quevedo, año 2014 - García Véloz, Kelly Lisbeth (2015)
The destruction of the environment, the high costs of pesticides and chemical fertilizers as well as the effects of the health of people is the main reason for introducing planting organic consumer market agricultural products, it should be noted that organic production is not alters the ecosystem around us, ensuring the consumer a product suitable for your health. The marketing of organic products will succeed because consumers today demand for healthy food products. Organic vegetables are produced without the use of agrochemicals, its management is performed with the use of organic fertilizers, natural insecticides, diversity of cropping. All this to save our environment (soil, plants, water, animals) and us as human beings in our favor food grown healthily. That is why this research is to create the company, so that in this way these products differently, processing them take advantage and getting food to market in the domestic market, and thus would be helping and creating sources work and a new alternative for increasing their income….